2014
DOI: 10.1021/ef502128s
|View full text |Cite
|
Sign up to set email alerts
|

Release and Transformation of Sodium during Pyrolysis of Zhundong Coals

Abstract: Zhundong coalfield is one of the superhuge coalfields newly discovered in Xinjiang Autonomous Region of China. While many studies on alkali metals in coal/biomass have been reported previously, few efforts were conducted on Zhundong coals which are characterized by a high content of sodium. It is challenging to explore the ash deposition problems related to Zhundong coals directly using existing findings on the behavior of alkali metals. The occurrence mode and transformation of alkali metals during thermal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…The literature [24] shows that the release of K and Na from well-characterized biofuels was quantified as a function of temperature in a lab-scale fixed-bed reactor. Wang et al [25] investigated the release and transformation fundamentals of sodium during pyrolysis of two Zhundong bituminous coals, with experimental results showing that the release of sodium increases with temperature, indicating that temperature has a profound effect on the volatilization of sodium. The range of temperatures was between 1200 and 1400 K. In this temperature range, the emission of pollutants, such as dioxin, can be controlled.…”
Section: Comparison Of Measured Results and Operating Parameters Of Tmentioning
confidence: 99%
“…The literature [24] shows that the release of K and Na from well-characterized biofuels was quantified as a function of temperature in a lab-scale fixed-bed reactor. Wang et al [25] investigated the release and transformation fundamentals of sodium during pyrolysis of two Zhundong bituminous coals, with experimental results showing that the release of sodium increases with temperature, indicating that temperature has a profound effect on the volatilization of sodium. The range of temperatures was between 1200 and 1400 K. In this temperature range, the emission of pollutants, such as dioxin, can be controlled.…”
Section: Comparison Of Measured Results and Operating Parameters Of Tmentioning
confidence: 99%
“…With an increase in combustion temperature, the water-soluble sodium gradually volatilized to the gas phase [13,14], and this volatilization of water-soluble sodium was the main cause of fouling during ash deposition. The ash fusion temperature was one of the commonly used indices for prediction of fouling caused by high-sodium coal, which was significantly affected by the mineral components in the coal.…”
Section: Introductionmentioning
confidence: 99%
“…So the ambient atmosphere also affects the volatilisation levels of the sodium species which shows that the oxidizing atmosphere inhibits the volatilization in some extent. In the study on the release and transformation of sodium during Pyrolysis of Zhundong Coals, Wang et al [27] also found that during the devolatilisation of Zhundong coals under CO 2 atmosphere, the release of sodium and its conversion into insoluble form will be inhibited compared to that under N 2 condition.…”
Section: Volatilisation Levels Of Sodium Species and Its Effect On Afmentioning
confidence: 99%